STRATA MANAGEMENT IN PENINSULAR MALAYSIA: AN OVERVIEW - Mohamad, Nor Asiah; Sufian, Azlinor; Mohamad, Mazliza (Pengarah Tanah dan Galian, 2015)
Strata properties law in Malaysia came into existence in 1985 and was governed by the Strata Titles Act 1985 (“STA”). To date, the Act has gone through various amendments. Nevertheless, it appears that the Act has failed to address the disputes arising from strata management and maintenance. The problem arises when parcel owners tend to look after their own private unit but neglect the common property which belongs to everybody. Consequently, landscaped areas become unattended, stairways become filthy and the building lack of proper maintenance. This paper discusses various amendments made; from the first amendment of the STA in 1990, second amendment in 1996, third amendment in 2001, the amendments in 2007 as well the latest amendment in 2013. The objective of this paper is to see whether the amendments to the existing legislations, including the Strata Management Act 2013 are sufficient enough to address the problems encountering the management of strata building in Malaysia. As such this paper will analyse some of the provisions in Building and Common Property (Maintenance and Management) Act 2007 (“BCPA”) and proposed Strata Management Act 2013. The research method used in writing up this paper is the qualitative research in which it analyses the relevant statutes, rules, regulations, books, journals, articles, thesis, seminar papers, electronic materials and various newspaper reports. The findings of the research suggest that irrespective of the newly introduced Strata Management Act 2013 there is a need for more legal improvements in order to create a better regulatory framework for strata management in Malaysia.